Preparation method of inorganic-organic composite binder for silicon negative electrode battery

By combining silicate inorganic binder and organic binder, a self-healing composite binder with a three-dimensional mesh structure was prepared, which solved the decomposition and insufficient binding force of the existing silicon negative electrode battery binder at high temperature. The problem is that the bonding performance and mechanical properties are significantly improved, and the high-temperature cycle stability and efficiency improvement of lithium-ion batteries are achieved.

CN119286435APending Publication Date: 2025-01-10YANGZHOU NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411379586.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing silicon negative electrode battery binder decomposes or oxidizes at high temperatures, and lacks binding force, resulting in shedding or peeling under external forces, and has low ionic conductivity, which cannot meet the application needs in high temperature environments.

Method used

The composite binder is prepared by silicon-rich silicate inorganic binder and organic binder. The combination of boric acid, lithium metasilicate, polyvinyl alcohol and biomass binder is formed with a three-dimensional network structure. Self-healing composite adhesives to enhance bonding and mechanical properties.

Benefits of technology

It significantly improves the bonding and mechanical properties of silicon negative electrode batteries, alleviates the mechanical stress caused by silicon volume expansion, maintains the stability of the electrode structure, and improves the cycle stability and efficiency of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005069565470000101
    Figure BDA0005069565470000101
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, in particular to a preparation method of an inorganic-organic composite binder for a silicon negative electrode battery. The modified chitosan is obtained by adding chitosan, ammoniated urushiol, an acetic acid solution and vanillin. And mixing the modified chitosan, guar gum, an acetic acid solution and glutaraldehyde to obtain the biomass binder. And adding deionized water to sequentially obtain a biomass binder solution, a boric acid solution, a lithium metasilicate solution and a polyvinyl alcohol solution. And adding the inorganic binder solution and the biomass binder solution into the polyvinyl alcohol solution, and fully stirring to obtain the composite binder. The composite binder prepared by the preparation method disclosed by the invention has good adhesive property and mechanical property, so that the composite binder has a wide application prospect in the technical field of lithium batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium batteries, in particular to a method for preparing an inorganic-organic composite binder for a silicon negative electrode battery. Background Art

[0002] Silicon has the advantages of abundant reserves, high theoretical specific capacity (4200mAh·g-1) and low working potential (~0.4Vvs.Li / Li+), and is expected to replace graphite as a new generation of high energy density lithium-ion battery negative electrode material. However, during the cycle, the volume change of silicon (>300%) seriously limits its commercial application. As one of the key components of battery materials, binders play an important role in maintaining the bonding between active materials, conductive agents and current collectors, and are currently a hot topic in the field of silicon negative electrode research. However, existing binders will decompose or oxidize at high temperatures, resulting in a decrease in their performance and unable to meet the application requirements in high temperature environments. The bonding force between the binder and the substrate is weak, and it is easy to fall off or peel off when subjected to external forces. There is a large resistance during ion conduction, resulting in energy loss and reduced efficiency. The ion conductivity is often low and cannot meet the requirements. Therefore, the present invention uses a silicate inorganic binder rich in silicon and an organic binder to prepare a composite binder, and systematically studies their effects on the bonding, dispersion and electrochemical properties of silicon-based negative electrodes.

[0003] In order to overcome the defects of the prior art, the present invention provides a method for preparing an inorganic-organic composite binder for a silicon negative electrode battery. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing an inorganic-organic composite binder for a silicon negative electrode battery to solve the problems in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A method for preparing an inorganic-organic composite binder for a silicon negative electrode battery comprises the following steps: mixing boric acid and deionized water, stirring at 25-30°C for 30-40 minutes to obtain a boric acid solution; mixing lithium metasilicate and deionized water, stirring at 25-30°C for 30-40 minutes to obtain a lithium metasilicate solution; mixing the boric acid solution and the lithium metasilicate solution to obtain an inorganic binder solution; adding polyvinyl alcohol to deionized water, stirring in an oil bath at 90-95°C for 2-3 hours to obtain a polyvinyl alcohol solution; adding the inorganic binder solution to the polyvinyl alcohol solution, stirring fully for 1-2 hours to prepare a composite binder.

[0007] More optimally, the concentration of the boric acid solution is 4-6wt%, the concentration of the lithium metasilicate solution is 4-6wt%, the concentration of the inorganic binder solution is 4-6wt%; and the concentration of the polyvinyl alcohol solution is 4-6wt%.

[0008] More optimally, the reaction mass ratio of the inorganic binder to polyvinyl alcohol is (0.25-1):5.

[0009] More optimally, the preferred reaction mass ratio of the inorganic binder to polyvinyl alcohol is 1:5.

[0010] More optimally, a biomass binder solution is prepared, and the biomass binder solution and the inorganic binder solution are added to the polyvinyl alcohol solution, and stirred for 1-2 hours to prepare a composite binder; the reaction mass ratio of the inorganic binder, the biomass binder and the polyvinyl alcohol is (0.5-2): (1-3): 10; the preparation process of the biomass binder solution:

[0011] S1: adding chitosan to a 1.2-1.5wt% acetic acid solution, stirring well to obtain a 1.5-1.7wt% chitosan solution; adding ammoniated urushiol to a 1.2-1.5wt% acetic acid solution, stirring well to obtain a 1.5-1.7wt% ammoniated urushiol solution; mixing vanillin, chitosan solution and ammoniated urushiol solution, stirring at a constant temperature of 70-80°C for 30-40min to obtain modified chitosan;

[0012] S2: Add modified chitosan and guar gum to 1.2-1.5wt% acetic acid solution, stir well to obtain a biomass solution; add glutaraldehyde to the biomass solution, stir and react at 80-85°C for 3-4h to obtain a biomass binder; mix the biomass binder and deionized water, stir at 25-30°C for 30-40min to obtain a 4-6wt% biomass binder solution.

[0013] More optimally, in step S1, when preparing the modified chitosan binder, the reaction mass ratio of vanillin, chitosan and ammoniated urushiol is (3.2-3.5): 1:1; the preparation process of ammoniated urushiol: add urushiol and cysteamine hydrochloride to ethanol, and then add 3-4wt% of benzil dimethyl ether, stir and react under ultraviolet light conditions for 5-6h, remove ethanol after the reaction, and then wash with potassium carbonate solution and sodium chloride solution to obtain ammoniated urushiol; the reaction molar ratio of urushiol and cysteamine hydrochloride is 1: (2.0-2.5); the ultraviolet light conditions are: wavelength 365nm, ultraviolet lamp power is 200-250W.

[0014] More optimally, in step S2, when preparing the biomass binder, the reaction mass ratio of modified chitosan, guar gum and glutaraldehyde is 1:1:(2-3).

[0015] The negative electrode sheet prepared by the composite binder comprises the following steps: uniformly mixing SiNPs and conductive carbon black, adding the mixture to the composite binder, stirring for 15-20 minutes at a temperature of 25-30°C and a rotation speed of 2000-2500rpm to obtain an electrode slurry; coating the electrode slurry on a surface of a copper foil, vacuum drying at 100-120°C for 12-14 hours, and heat treating at 300-320°C for 6-8 hours to obtain a negative electrode sheet; in the negative electrode sheet after heat treatment, the mixing mass ratio of SiNPs, conductive carbon black and composite binder is 8:1:1.

[0016] The lithium-ion battery prepared by the negative electrode sheet comprises the following steps: assembling the positive electrode sheet, the negative electrode sheet and the isolation membrane by stacking, placing the assembled components into a battery casing, injecting a LiPF6 electrolyte with a concentration of 1.08-1.10 mol / kg into the battery casing, and then sealing and packaging to obtain a lithium-ion battery.

[0017] Beneficial effects of the present invention:

[0018] The invention obtains modified chitosan by adding chitosan, ammoniated urushiol, acetic acid solution and vanillin. The modified chitosan, guar gum, acetic acid solution and glutaraldehyde are mixed to obtain a biomass binder. Deionized water is then added to obtain a biomass binder solution, a boric acid solution, a lithium metasilicate solution and a polyvinyl alcohol solution in sequence. The inorganic binder solution and the biomass binder solution are added to the polyvinyl alcohol solution, and the composite binder is obtained by fully stirring.

[0019] The present invention is characterized in that, in step S1, chitosan and ammoniated urushiol are pretreated with acetic acid solution respectively to obtain chitosan solution and ammoniated urushiol solution; vanillin, chitosan solution and ammoniated urushiol solution are mixed, and the modified chitosan is obtained by constant temperature stirring. In this step, the surfaces of chitosan and ammoniated urushiol contain a large number of amino groups, so under suitable reaction conditions, they can react with vanillin containing aldehyde groups to undergo Schiff base reaction, cross-link with each other to form a three-dimensional network structure, and by forming huge interconnection points, the stress generated by volume expansion can be dispersed during the cycle, and the high mechanical stress generated by the volume change of silicon during repeated cycles can be continuously dissipated, thereby maintaining the structural stability of the silicon electrode. In addition, the modified chitosan can also produce hydrogen bond interactions with the hydroxyl groups on the surface of the silicon negative electrode, thereby forming a more solid bonding interface and significantly improving the bonding performance.

[0020] The characteristics of the present invention are that, in step S2, modified chitosan, guar gum, acetic acid solution, glutaraldehyde are mixed to obtain a biomass binder. The reaction principle of this step is that modified chitosan, guar gum and glutaraldehyde containing a large amount of hydroxyl groups undergo aldol condensation reaction to obtain a biomass binder with a 3D cross-linked network structure. On the one hand, because it has a huge interlaced network structure, the mechanical stress produced by the large volume change of Si in the cycle process can be effectively alleviated to the destruction of the electrode structure. On the other hand, the biomass binder is made based on the natural materials of plants, animals or microorganisms, and compared with traditional chemical binders, significantly reduces the dependence on limited fossil resources), supports the use of renewable resources.

[0021] Finally, the inorganic binder solution and the biomass binder solution are added to the polyvinyl alcohol solution and stirred thoroughly to obtain a composite binder. By using boric acid as a cross-linking agent, the inorganic binder solution and the biomass binder solution containing a large amount of hydroxyl groups are cross-linked with the polyvinyl alcohol also containing a large amount of hydroxyl groups to prepare a self-healing composite binder with a three-dimensional network structure, thereby effectively alleviating the volume expansion of silicon and maintaining the stability of the electrode structure. In summary, the composite binder prepared by the present invention has good bonding properties and mechanical properties, and therefore has broad application prospects in the field of lithium battery technology. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Source of raw materials:

[0024] Urushiol, provided by Hubei Maidehao Biotechnology Co., Ltd., model MDH; chitosan, provided by Qingdao Bozhihuili Biotechnology Co., Ltd., model J-67; guar gum, provided by Shandong Shengbei Chemical Co., Ltd., with an active ingredient content of 99%; silicon nanoparticles SiNPs, provided by Shanghai Shuitian Material Technology Co., Ltd., with a specification of -100nm; polyvinylidene fluoride, provided by Dongguan Zhongyuan Plastic Raw Materials Co., Ltd., with a specification of AR; sodium alginate, provided by Zhejiang Bodanheng Biotechnology, with a specification of AR; sodium carboxymethyl cellulose, provided by Sigma-Aldrich Trading Co., Ltd., with a specification of AR; polyvinyl alcohol, provided by Sinopharm Chemical Reagent Co., Ltd., with a specification of 1800; boric acid, provided by Shanghai Aladdin Biochemical Technology Co., Ltd., with a specification of AR.

[0025] Example 1: The reaction mass ratio of the inorganic binder and polyvinyl alcohol is 2:10;

[0026] Step 1: Mix boric acid and deionized water, stir at 30°C for 40 minutes to obtain a 4wt% boric acid solution; mix lithium metasilicate and deionized water, stir at 30°C for 40 minutes to obtain a 4wt% lithium metasilicate solution;

[0027] The boric acid solution and the lithium metasilicate solution were mixed to obtain a 4wt% inorganic binder solution; polyvinyl alcohol was added to deionized water, and stirred in an oil bath at 95°C for 3h to obtain a 4wt% polyvinyl alcohol solution; the inorganic binder solution was added to the polyvinyl alcohol solution, and stirred for 2h to prepare a composite binder; wherein the reaction mass ratio of the inorganic binder to the polyvinyl alcohol was 2:10;

[0028] Step 2: Mix SiNPs and conductive carbon black evenly, then add the mixture to the composite binder, stir for 20 minutes at a temperature of 30°C and a rotation speed of 2500rpm to obtain an electrode slurry; apply the electrode slurry to the surface of the copper foil, and then vacuum dry it at 120°C for 14 hours to obtain a negative electrode sheet; wherein the mixing mass ratio of SiNPs, conductive carbon black and composite binder is 8:1:1; stack the positive electrode sheet, the negative electrode sheet and the isolation membrane, put the assembled parts into a battery casing, inject a LiPF6 electrolyte with a concentration of 1.08 mol / kg into the battery casing, and then seal and package to obtain a lithium-ion battery.

[0029] Example 2: The reaction mass ratio of the inorganic binder and polyvinyl alcohol is 0.5:10;

[0030] Step 1: Mix boric acid and deionized water, stir at 30°C for 40 minutes to obtain a 4wt% boric acid solution; mix lithium metasilicate and deionized water, stir at 30°C for 40 minutes to obtain a 4wt% lithium metasilicate solution;

[0031] The boric acid solution and the lithium metasilicate solution are mixed to obtain a 4wt% inorganic binder solution; polyvinyl alcohol is added to deionized water, and stirred in an oil bath at 95°C for 3h to obtain a 4wt% polyvinyl alcohol solution; the inorganic binder solution is added to the polyvinyl alcohol solution, and stirred for 2h to prepare a composite binder; wherein the reaction mass ratio of the inorganic binder to the polyvinyl alcohol is 0.5:10;

[0032] Step 2: Mix SiNPs and conductive carbon black evenly, then add the mixture to the composite binder, stir for 20 minutes at a temperature of 30°C and a rotation speed of 2500rpm to obtain an electrode slurry; apply the electrode slurry to the surface of the copper foil, and then vacuum dry it at 120°C for 14 hours to obtain a negative electrode sheet; wherein the mixing mass ratio of SiNPs, conductive carbon black and composite binder is 8:1:1; stack the positive electrode sheet, the negative electrode sheet and the isolation membrane, put the assembled parts into a battery casing, inject a LiPF6 electrolyte with a concentration of 1.08 mol / kg into the battery casing, and then seal and package to obtain a lithium-ion battery.

[0033] Example 3: The reaction mass ratio of the inorganic binder and polyvinyl alcohol is 1:10;

[0034] Step 1: Mix boric acid and deionized water, stir at 30°C for 40 minutes to obtain a 4wt% boric acid solution; mix lithium metasilicate and deionized water, stir at 30°C for 40 minutes to obtain a 4wt% lithium metasilicate solution;

[0035] The boric acid solution and the lithium metasilicate solution are mixed to obtain a 4wt% inorganic binder solution; polyvinyl alcohol is added to deionized water, and stirred in an oil bath at 95°C for 3h to obtain a 4wt% polyvinyl alcohol solution; the inorganic binder solution is added to the polyvinyl alcohol solution, and stirred for 2h to prepare a composite binder; wherein the reaction mass ratio of the inorganic binder to the polyvinyl alcohol is 1:10;

[0036] Step 2: Mix SiNPs and conductive carbon black evenly, then add the mixture to the composite binder, stir for 20 minutes at a temperature of 30°C and a rotation speed of 2500rpm to obtain an electrode slurry; apply the electrode slurry to the surface of the copper foil, and then vacuum dry it at 120°C for 14 hours to obtain a negative electrode sheet; wherein the mixing mass ratio of SiNPs, conductive carbon black and composite binder is 8:1:1; stack the positive electrode sheet, the negative electrode sheet and the isolation membrane, put the assembled parts into a battery casing, inject a LiPF6 electrolyte with a concentration of 1.08 mol / kg into the battery casing, and then seal and package to obtain a lithium-ion battery.

[0037] Example 4: The reaction mass ratio of the inorganic binder and polyvinyl alcohol is 10:10;

[0038] Step 1: Mix boric acid and deionized water, stir at 30°C for 40 minutes to obtain a 4wt% boric acid solution; mix lithium metasilicate and deionized water, stir at 30°C for 40 minutes to obtain a 4wt% lithium metasilicate solution;

[0039] The boric acid solution and the lithium metasilicate solution were mixed to obtain a 4wt% inorganic binder solution; polyvinyl alcohol was added to deionized water, and stirred in an oil bath at 95°C for 3h to obtain a 4wt% polyvinyl alcohol solution; the inorganic binder solution was added to the polyvinyl alcohol solution, and stirred for 2h to prepare a composite binder; wherein the reaction mass ratio of the inorganic binder to the polyvinyl alcohol was 10:10;

[0040] Step 2: Mix SiNPs and conductive carbon black evenly, then add the mixture to the composite binder, stir for 20 minutes at a temperature of 30°C and a rotation speed of 2500rpm to obtain an electrode slurry; apply the electrode slurry to the surface of the copper foil, and then vacuum dry it at 120°C for 14 hours to obtain a negative electrode sheet; wherein the mixing mass ratio of SiNPs, conductive carbon black and composite binder is 8:1:1; stack the positive electrode sheet, the negative electrode sheet and the isolation membrane, put the assembled parts into a battery casing, inject a LiPF6 electrolyte with a concentration of 1.08 mol / kg into the battery casing, and then seal and package to obtain a lithium-ion battery.

[0041] Example 5: Adding an inorganic binder solution and a biomass binder solution to a polyvinyl alcohol solution to prepare a composite binder;

[0042] Step 1: Add urushiol and cysteamine hydrochloride to ethanol, then add 4wt% benzil dimethyl ether, stir and react for 6h under ultraviolet light, remove ethanol after the reaction, wash with potassium carbonate solution and sodium chloride solution to obtain ammoniated urushiol; the reaction molar ratio of urushiol and cysteamine hydrochloride is 1:2.3; the ultraviolet light conditions are: wavelength 365nm, ultraviolet lamp power 250W;

[0043] Add chitosan to 1.2wt% acetic acid solution, stir well to obtain 1.5wt% chitosan solution; add ammoniated urushiol to 1.2wt% acetic acid solution, stir well to obtain 1.5wt% ammoniated urushiol solution; mix vanillin, chitosan solution and ammoniated urushiol solution, stir at 80℃ for 40min to obtain modified chitosan; wherein the reaction mass ratio of vanillin, chitosan and ammoniated urushiol is 3.5:1:1;

[0044] Step 2: adding modified chitosan and guar gum to 1.2wt% acetic acid solution, stirring thoroughly to obtain a biomass solution; adding glutaraldehyde to the biomass solution, stirring at 85°C for 4h to obtain a biomass binder; mixing the biomass binder and deionized water, stirring at 30°C for 40min to obtain a 4wt% biomass binder solution; wherein the reaction mass ratio of modified chitosan, guar gum and glutaraldehyde is 1:1:2;

[0045] Step 3: Mix boric acid and deionized water, stir at 30°C for 40 minutes to obtain a 4wt% boric acid solution; mix lithium metasilicate and deionized water, stir at 30°C for 40 minutes to obtain a 4wt% lithium metasilicate solution;

[0046] The boric acid solution and the lithium metasilicate solution were mixed to obtain a 4wt% inorganic binder solution; polyvinyl alcohol was added to deionized water, and stirred in an oil bath at 95°C for 3h to obtain a 4wt% polyvinyl alcohol solution; the inorganic binder solution and the biomass binder solution were sequentially added to the polyvinyl alcohol solution, and stirred for 2h to prepare a composite binder; wherein the reaction mass ratio of the inorganic binder, the biomass binder and the polyvinyl alcohol was 2:1.5:10;

[0047] Step 4: Mix SiNPs and conductive carbon black evenly, then add the mixture to the composite binder, stir for 20 minutes at a temperature of 30°C and a rotation speed of 2500rpm to obtain an electrode slurry; apply the electrode slurry to the surface of the copper foil, and then vacuum dry it at 120°C for 14 hours to obtain a negative electrode sheet; wherein the mixing mass ratio of SiNPs, conductive carbon black and composite binder is 8:1:1; stack the positive electrode sheet, the negative electrode sheet and the isolation membrane, put the assembled parts into a battery casing, inject a LiPF6 electrolyte with a concentration of 1.08 mol / kg into the battery casing, and then seal and package to obtain a lithium-ion battery.

[0048] Comparative Example 1: The composite binder is replaced with sodium alginate binder, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: Mix SiNPs and conductive carbon black evenly, and then add the mixture to the sodium alginate binder, stir for 20 minutes at a temperature of 30°C and a rotation speed of 2500rpm to obtain an electrode slurry; apply the electrode slurry to the surface of the copper foil, and then vacuum dry it at 120°C for 14 hours to obtain a negative electrode sheet; wherein the mixing mass ratio of SiNPs, conductive carbon black and sodium alginate binder is 8:1:1; stack and assemble the positive electrode sheet, the negative electrode sheet and the isolation membrane, put the assembled components into a battery casing, inject a LiPF6 electrolyte with a concentration of 1.08 mol / kg into the battery casing, and then seal and package to obtain a lithium-ion battery.

[0049] Comparative Example 2: The composite binder is replaced with a polyvinylidene fluoride binder, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: Mix SiNPs and conductive carbon black evenly, and then add the mixture to the polyvinylidene fluoride binder, and stir for 20 minutes at a temperature of 30°C and a rotation speed of 2500rpm to obtain an electrode slurry; the electrode slurry is coated on the surface of the copper foil, and then vacuum dried at 120°C for 14 hours to obtain a negative electrode sheet; wherein the mixing mass ratio of SiNPs, conductive carbon black and polyvinylidene fluoride binder is 8:1:1; the positive electrode sheet, the negative electrode sheet and the isolation membrane are stacked and assembled, the assembled components are placed in a battery casing, and a LiPF6 electrolyte with a concentration of 1.08 mol / kg is injected into the battery casing, and then a lithium-ion battery is obtained by sealing and packaging.

[0050] Comparative Example 3: The composite binder is replaced with sodium carboxymethyl cellulose binder, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: Mix SiNPs and conductive carbon black evenly, and then add the mixture to the sodium carboxymethyl cellulose binder, and stir for 20 minutes at a temperature of 30°C and a rotation speed of 2500rpm to obtain an electrode slurry; the electrode slurry is applied to the surface of the copper foil, and then vacuum dried at 120°C for 14 hours to obtain a negative electrode sheet; wherein the mixing mass ratio of SiNPs, conductive carbon black and sodium carboxymethyl cellulose binder is 8:1:1; the positive electrode sheet, the negative electrode sheet and the isolation membrane are stacked and assembled, the assembled components are placed in a battery casing, and a LiPF6 electrolyte with a concentration of 1.08 mol / kg is injected into the battery casing, and then a lithium-ion battery is obtained by sealing and packaging.

[0051] Comparative Example 4: The composite binder is replaced with a polyvinyl alcohol binder, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: Mix SiNPs and conductive carbon black evenly, and then add the mixture to the polyvinyl alcohol binder, and stir for 20 minutes at a temperature of 30°C and a rotation speed of 2500rpm to obtain an electrode slurry; the electrode slurry is applied to the surface of the copper foil, and then vacuum dried at 120°C for 14 hours to obtain a negative electrode sheet; wherein the mixing mass ratio of SiNPs, conductive carbon black and polyvinyl alcohol binder is 8:1:1; the positive electrode sheet, the negative electrode sheet and the isolation membrane are stacked and assembled, the assembled components are placed in a battery casing, and a LiPF6 electrolyte with a concentration of 1.08 mol / kg is injected into the battery casing, and then a lithium-ion battery is obtained by sealing and packaging.

[0052] Comparative Example 5: The composite binder is replaced with an LS-CA binder (wherein LS is lithium metasilicate and CA is citric acid), and the rest is the same as Example 1, and the specific steps are as follows: Step 1: Mix LS lithium metasilicate and deionized water, stir at 30°C for 40 minutes, and obtain a 4wt% LS solution; Mix the LS solution and 0.1mol / L citric acid solution in a mass ratio of 1:1, stir at 30°C for 5 minutes, and obtain a 4wt% LS-CA binder with a pH of 4.5;

[0053] Step 2: Mix SiNPs and conductive carbon black evenly, then add the mixture to the LS-CA binder, stir for 20 minutes at a temperature of 30°C and a rotation speed of 2500rpm to obtain an electrode slurry; apply the electrode slurry to the surface of the copper foil, and then vacuum dry it at 120°C for 14 hours to obtain a negative electrode sheet; the mixing mass ratio of SiNPs, conductive carbon black and LS-CA binder is 8:1:1; stack the positive electrode sheet, the negative electrode sheet and the isolation membrane, put the assembled parts into a battery casing, inject a LiPF6 electrolyte with a concentration of 1.08 mol / kg into the battery casing, and then seal and package to obtain a lithium-ion battery.

[0054] Comparative Example 6: The composite binder is replaced with LS-CA binder and a heat treatment at 300°C is added. The rest is the same as Example 1, and the specific steps are as follows: Step 1: LS lithium metasilicate and deionized water are mixed, and stirred at 30°C for 40 minutes to obtain a 4wt% LS solution; the LS solution and 0.1mol / L citric acid solution are mixed in a mass ratio of 1:1, and stirred at 30°C for 5 minutes to obtain a 4wt% LS-CA binder with a pH of 4.5;

[0055] Step 2: Mix SiNPs and conductive carbon black evenly, then add the mixture to the LS-CA binder, stir for 20 minutes at a temperature of 30°C and a rotation speed of 2500rpm to obtain an electrode slurry; apply the electrode slurry to the surface of the copper foil, and then vacuum dry it at 120°C for 14 hours and heat treat it at 320°C for 8 hours to obtain a negative electrode sheet; in the negative electrode sheet after heat treatment, the mixing mass ratio of SiNPs, conductive carbon black and LS-CA binder is 8:1:1; stack the positive electrode sheet, the negative electrode sheet and the isolation membrane, put the assembled parts into a battery casing, inject a LiPF6 electrolyte with a concentration of 1.08 mol / kg into the battery casing, and then seal and package it to obtain a lithium-ion battery.

[0056] Detection test:

[0057] Peel force test: This paper uses Zwick's Zwick / Roell Z020 universal material testing machine to perform a peel test on the electrode, and then analyzes the peel force of silicon electrodes prepared with different adhesives.

[0058] Initial capacitance test: Constant current charge and discharge test uses LAND battery test system with voltage window range of 0.005-1.2V.

[0059] 2C current cycle 50 cycles discharge capacity test: The cycle performance and rate performance of the half-cell need to be activated for 50 cycles at a current density of 2C (1C = 4200mAhg-1), where the battery CV curve is recorded by CHI760E, with a voltage window range of 0.005-1.2V and a voltage scan rate of 0.1mVs-1. The battery EIS is also tested using CHI760E, with a frequency range of 0.01-100kHZ and an amplitude of 5mV. The results are as follows:

[0060]

[0061] Conclusion: Analysis of Example 1-Example 4: Data analysis shows that when the inorganic binder and polyvinyl alcohol react in a reaction mass ratio of 2:10, covalent and non-covalent crosslinking can effectively occur, significantly improving the solution viscosity, and the peel force, initial capacitance and discharge capacity after 50 cycles of 2C current are better.

[0062] Analysis of Example 5: This example is a preferred example of the present invention, and the peeling force, initial capacitance and discharge capacity after 50 cycles of 2C current are optimal.

[0063] Analysis of Comparative Examples 1-4: In Comparative Examples 1-4, the composite binder is replaced with sodium alginate binder, polyvinylidene fluoride binder, sodium carboxymethyl cellulose binder, and polyvinyl alcohol binder, respectively. It can be seen from the data that the binders prepared by the present invention have good bonding properties. At the same time, the 3D network structure of the composite binder can effectively alleviate the huge volume change of the silicon negative electrode. Therefore, compared with Example 1, the peeling force, initial capacitance and discharge capacity after 50 cycles of 2C current are all reduced.

[0064] Analysis of Comparative Examples 5 and 6: When the composite binder is replaced with LS-CA binder and heat treated at 300°C, the silicon electrode exhibits better electrical cycle stability, and the bonding force is higher than that of sodium alginate binder, sodium carboxymethyl cellulose binder, and polyvinyl alcohol binder. This indicates that lithium metasilicate not only plays a bonding role, but also can improve the lithium ion transmission capacity within the electrode, thereby achieving the cycle stability of the silicon negative electrode at high current density.

[0065] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.

[0066] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing an inorganic-organic composite binder for a silicon negative electrode battery, characterized in that: The following steps are involved: Mix boric acid and deionized water, stir at 25-30°C for 30-40 minutes to obtain a boric acid solution; mix lithium metasilicate and deionized water, stir at 25-30°C for 30-40 minutes to obtain a lithium metasilicate solution; mix the boric acid solution and the lithium metasilicate solution to obtain an inorganic binder solution; add polyvinyl alcohol to deionized water, stir at 90-95°C in an oil bath for 2-3 hours to obtain a polyvinyl alcohol solution; The inorganic binder solution is added to the polyvinyl alcohol solution and stirred for 1-2 hours to prepare a composite binder.

2. The method for preparing an inorganic-organic composite binder for a silicon negative electrode battery according to claim 1, characterized in that: The concentration of the boric acid solution is 4-6wt%, the concentration of the lithium metasilicate solution is 4-6wt%, the concentration of the inorganic binder solution is 4-6wt%; and the concentration of the polyvinyl alcohol solution is 4-6wt%.

3. The method for preparing an inorganic-organic composite binder for a silicon negative electrode battery according to claim 1, characterized in that: The reaction mass ratio of the inorganic binder to the polyvinyl alcohol is (0.25-1):

5.

4. The method for preparing an inorganic-organic composite binder for a silicon negative electrode battery according to claim 3, characterized in that: The reaction mass ratio of the inorganic binder to the polyvinyl alcohol is 1:

5.

5. The method for preparing an inorganic-organic composite binder for a silicon negative electrode battery according to claim 1, characterized in that: The composite binder also includes a biomass binder solution. The biomass binder solution and the inorganic binder solution are added to the polyvinyl alcohol solution and stirred for 1-2 hours to prepare the composite binder. The reaction mass ratio of the inorganic binder, the biomass binder and the polyvinyl alcohol is (0.5-2): (1-3):

10. Preparation process of biomass binder solution: S1: adding chitosan to a 1.2-1.5wt% acetic acid solution, stirring well to obtain a 1.5-1.7wt% chitosan solution; adding ammoniated urushiol to a 1.2-1.5wt% acetic acid solution, stirring well to obtain a 1.5-1.7wt% ammoniated urushiol solution; mixing vanillin, chitosan solution and ammoniated urushiol solution, stirring at a constant temperature of 70-80°C for 30-40min to obtain modified chitosan; S2: Add modified chitosan and guar gum to 1.2-1.5wt% acetic acid solution, stir well to obtain a biomass solution; add glutaraldehyde to the biomass solution, stir and react at 80-85°C for 3-4h to obtain a biomass binder; mix the biomass binder and deionized water, stir at 25-30°C for 30-40min to obtain a 4-6wt% biomass binder solution.

6. The method for preparing an inorganic-organic composite binder for a silicon negative electrode battery according to claim 5, characterized in that: In step S1, when preparing the modified chitosan binder, the reaction mass ratio of vanillin, chitosan and ammoniated urushiol is (3.2-3.5): 1: 1; the preparation process of ammoniated urushiol: add urushiol and cysteamine hydrochloride to ethanol, and then add 3-4wt% of benzil dimethyl ether, stir and react for 5-6h under ultraviolet light conditions, remove ethanol after the reaction, and then wash with potassium carbonate solution and sodium chloride solution to obtain ammoniated urushiol; the reaction molar ratio of urushiol and cysteamine hydrochloride is 1: (2.0-2.5); the ultraviolet light conditions are: wavelength 365nm, ultraviolet lamp power is 200-250W.

7. The method for preparing an inorganic-organic composite binder for a silicon negative electrode battery according to claim 5, characterized in that: In step S2, when preparing the biomass binder, the reaction mass ratio of modified chitosan, guar gum and glutaraldehyde is 1:1:(2-3).

8. An inorganic-organic composite binder for silicon negative electrode batteries, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 7.

9. The negative electrode sheet prepared by the composite binder according to claim 8, characterized in that: The following steps are involved: SiNPs and conductive carbon black are mixed evenly, and the mixture is added to the composite binder, and stirred for 15-20 minutes at a temperature of 25-30°C and a rotation speed of 2000-2500rpm to obtain an electrode slurry; the electrode slurry is coated on the surface of a copper foil, and then vacuum dried at 100-120°C for 12-14h and heat treated at 300-320°C for 6-8h to obtain a negative electrode sheet; in the negative electrode sheet after heat treatment, the mixing mass ratio of SiNPs, conductive carbon black and composite binder is 8:1:

1.

10. A lithium-ion battery prepared using the negative electrode sheet according to claim 9, characterized in that: The following steps are involved: The positive electrode sheet, the negative electrode sheet and the isolation membrane are stacked and assembled, and the assembled parts are placed in a battery casing, and a LiPF6 electrolyte with a concentration of 1.08-1.10 mol / kg is injected into the battery casing, and then the lithium-ion battery is obtained by sealing and packaging.

Citation Information

Cited By

  • Adhesive and preparation method thereof, negative pole piece, battery and electric equipment

    CN120005539A

  • Adhesive and its preparation method, negative electrode sheet, battery and electrical equipment

    CN120005539B

  • Water-based binder for carbon-coated aluminum foil of lithium ion battery and preparation method of water-based binder

    CN120365864A